The effects and significance of gut microbiota and its metabolites on the regulation of osteoarthritis: Close coordination of gut-bone axis - Liu, Lei; Tian, Feng; Li, Guo-Yuan; Xu, Wei; Xia, Rui (Frontiers in Nutrition, 2022)
Osteoarthritis (OA) is a common chronic degenerative disease of articular cartilage in middle-aged and older individuals, which can result in the joint pain and dysfunction, and even cause the joint deformity or disability. With the enhancing process of global aging, OA has gradually become a major public health problem worldwide. Explaining pathogenesis of OA is critical for the development of new preventive and therapeutic interventions. In recent years, gut microbiota (GM) has been generally regarded as a “multifunctional organ”, which is closely relevant with a variety of immune, metabolic and inflammatory functions. Meanwhile, more and more human and animal researches have indicated the existence of gut-bone axis and suggested that GM and its metabolites are closely involved in the pathogenic process of OA, which might become a potential and promising intervention target. Based on the close coordination of gut-bone axis, this review aims to summarize and discuss the mechanisms of GM and its metabolites influencing OA from the aspects of the intestinal mucosal barrier modulation, intestinal metabolites modulation, immune modulation and strategies for the prevention or treatment of OA based on perspectives of GM and its metabolites, thus providing a profound knowledge and recognition of it.